Answer:
The equation is x = 4y + 13
Step-by-step explanation:
* Lets talk about the parametric equations
- Parametric equations are a set of equations that express a set
of quantities as explicit functions of a number of independent
variables
- Ex: x = at + b and y = ct + d are parametric equations
- We use them to find relation between the variables x and y
* Lets solve the problem
∵ x = 4t + 1 ⇒ (1)
∵ y = t - 3 ⇒ (2)
- The parameter is t to eliminate it find t in terms of x or y
- We will use equation (2) to find t in terms of y
∵ y = t - 3 ⇒ add 3 to both sides
∴ t = y + 3 ⇒ (3)
- Substitute the value of t in equation (3) in equation (1)
∵ x = 4t + 1
∵ t = y + 3
∴ x = 4(y + 3) + 1 ⇒ open the bracket
∴ x = 4y + 12 + 1 ⇒ add like term
∴ x = 4y + 13
* The equation is x = 4y + 13
Answer:
C. as likely as not
Step-by-step explanation:
The teacher makes two groups with the same number and divides the student at random. The two groups have equal size, so the chance for someone to get picked into group 1 is 100%/2= 50%. The chance for someone to get picked into group 2 will be also 100%/2= 50%
The chance to get picked to be in group 1(50%) is the same as the chance to NOT get picked into group 1(50%). The word to explain this chance will be "as likely as not".
Answer:
the greatest common factor is 3
Answer:
The answer to this question is 3
Step-by-step explanation:
the answer is 3
x + y = 4
Y= x+4
Using elimination
Answer:
Step-by-step explanation:
In this question we need to assume the side length of each quilt
Quilt 1 has the area of: 3*3 = 9 square cm and the perimeter: 3+3+3+3 = 12 cm
Quilt has has the area of: 4*4 = 19 square cm and the perimeter: 4+4+4+4 = 16 cm
So you can see the quilts have different perimeter, and areas
A. Transitive Property
B. Multiplicative Identity
C. Communicative Property of Multiplication
D. Reflexive Property
Answer:
A. Transitive Property
N CH-7=5X
Answer:
x = 11 and
Step-by-step explanation:
If LMNO is a parallelogram then it's opposite sides will be equal.
So, LM = ON
⇒ 4x + 4 = 5x - 7
⇒ x = 11
Now, MN = OL
⇒ x - 7 = 3y - 4
⇒ 11 - 7 = 3y - 4 {Since we already have, x = 11}
⇒ (Answer)